Long non‐coding RNA activated by transforming growth factor‐β promotes proliferation and invasion of cervical cancer cells by regulating the miR‐144/ITGA6 axis. Issue 6 (8th April 2019) - Zhu, Yingping; Wu, Yanping; Yang, Liwei; Dou, Xiaoqing; Jiang, Jun; Wang, Liangping
Abstract : New Findings: What is the central question of this study? This study was designed to investigate the molecular mechanism and biological roles of long non‐coding RNA activated by transforming growth factor‐β (lncRNA ATB) in the progression of cervical cancer. What is the main finding and its importance? Our study provided new insight into the cross‐talk between lncRNA ATB, miR‐144 and ITGA6, shedding light on the therapy for cervical cancer. Abstract: The present study was designed to investigate the molecular mechanism and biological roles of long non‐coding RNA activated by transforming growth factor‐β (lncRNA ATB) in the progression of cervical cancer. The expression levels of lncRNA ATB, miR‐144 and integrin α6 (ITGA6) were detected in human cervical cancer cell lines using quantitative real‐time PCR and western blotting. Cell viability was quantified by MTT assay at 12, 24, 36, 48 and 72 h after transfection, and cell invasion was determined by the Transwell migration assay. The association among lncRNA ATB, miR‐144 and ITGA6 was disclosed by a dual‐luciferase reporter assay. We found that lncRNA ATB was highly expressed in human cervical cancer cell lines. Further investigation indicated that lncRNA ATB functioned as a competitive endogenous RNA (ceRNA) for miR‐144 to promote cervical cancer cell proliferation and invasion. We demonstrated that ITGA6 was a direct target of miR‐144, and lncRNA ATB facilitated the proliferation and invasion of cervical cancer cells via the miR‐144/ITGA5 axis. In conclusion, the lncRNA ATB/miR‐144/ITGA6 axis might be a promising therapeutic target for cervical cancer. Abstract :